n-Butyldichlorido{4-cyclohexyl-1-[1-(pyridin 2-yl-jN)ethylidene]thiosemicarbazidato-j2N1,S}tin(IV) - Md. Abu, Affan; Abdus, Salam; Mohd Razip, Asaruddin; Tiekink, Edward (IUCR, 2012)
Two independent mol-ecules comprise the asymmetric unit in the title compound, [Sn(C₄H₉)(C₁₄H₁₉N₄S)Cl₂]. In each mol-ecule, the Sn(IV) atom exists within a distorted octa-hedral geometry defined by the N,N',S-tridentate mono-deprotonated Schiff base ligand, two mutually trans Cl atoms, and the α-C atom of the n-butyl group; the latter is trans to the azo-N atom. The greatest distortion from the ideal geometry is found in the nominally trans angle formed by the S and pyridyl-N atoms at Sn [151.72 (7) and 152.04 (7)°, respectively]. In the crystal, mol-ecules are consolidated into a three-dimensional architecture by a combination of N-H⋯Cl, C-H⋯π and π-π inter-actions [inter-centroid distances = 3.6718 (19) and 3.675 (2) Å].